Citric Acid Production From Toba Banana Peel (Musa acuminata Colla) Through Submerged Fermentation Using Aspergillus niger - MEVA GUSTINA E. SIDAURUK; SURYA NINGSIH HUTAURUK; MERRY MERYAM MARTGRITA; ADELINA MANURUNG (Indonesian Society for microbiology, 2019)
Toba banana peel waste is derived from Toba banana fruit (Musa acuminata Colla) processing. Local people utilized banana peel waste usually as livestock feed. The waste also can make an environmental problem if it is not handling well. Banana peel waste has a high content of carbohydrate that can be fermented to produce a more valuable product, one of which is citric acid. Citric acid is an organic acid that is consumed globally and produced in large quantities. In food and beverages industries, citric acid is used for various purposes due to its high solubility, non-toxic and good taste characteristics. The objective of this research is to determine the optimum conditions of submerged fermentation of banana peel to produce citric acid using Aspergillus niger. The treatments were various banana peel concentrations (5%, 10% and 15% w/v) added with 5% sucrose or 5% glucose (w/v). During the fermentation, pH was measured to determine pH changes indicated the production of citric acid. The results showed that the variation concentration of banana peel substrate and type of sugars affect citric acid production. The optimum condition of submerged fermentation by Aspergillus niger was obtained at 15% substrate concentration by adding 5% sucrose to produce 0.651% (w/v) of citric acid.